Morfometrik Dan Meristik Jenis-Jenis Ikan Ordo Perciformes di Muara Sungai Banyuasin Kabupaten Banyuasin Sumatera Selatan - Wahyu Wahyu; Syaiful Eddy; Dian Mutiara (Indobiosains, 2021)
Morphometric and Meristic research on the types of fish of the order Perciformes in the Banyuasin River Estuary, Banyuasin Regency, South Sumatra Province, was carried out in March-April 2021. Sampling was carried out using the purposive sampling method by following fishermen exploring water areas where there were estimated to be a lot of fish. The fishing gear used is nets, fishing rods, fishing rods and traps. The fish obtained were photographed and preserved in a coolbox with 10% formalin. Fish were identified and classified in the Biology laboratory of PGRI Palembang University. The types of fish of the order Perciformes obtained consisted of Familia Latidae species Lates calcarifer, family Scatophagidae species Scatophagus argus, family Serranidae species Epinephelus coiodes, familia Polynemidae species Eleutheronema tetradactylum.Keywords: Perciformes, Morphometric, Meristic, Banyuasin River Estuary.